Fatigue Crack Growth Detect - Assess - Avoid - Richard, Hans Albert; Sander, Manuela (Solid Mechanics and Its Applications,, 2016)
This book offers a concise introduction to fatigue crack growth, based on practical examples. It discusses the essential concepts of fracture mechanics, fatigue crack growth under constant and variable amplitude loading and the determination of the fracture-mechanical material parameters. The book also introduces the analytical and numerical simulation of fatigue crack growth as well as crack initiation. It concludes with a detailed description of several practical case studies and some exercises. The target group includes graduate students, researchers at universities and practicing engineers.